Peer Corrective Feedback: Face-saving Strategies in Teletandem Oral Sessions - CAVALARI, Suzi Marques Spatti; FRESCHI, Ana Carolina; PEREIRA FILHO, Sidnei Antonio (The ESPecialist, 2022)
This paper aims at examining oral peer feedback in relation to facework theories within the teletandem context. Teletandem is a mode of telecollaboration in which two learners who speak different languages meet virtually in order to learn with each other by offering feedback by means of audio, video and textual resources. The study is qualitative in nature and uses an ethnographic microanalysis approach. The data utilized are recordings of 20 teletandem oral sessions stored in MulTeC (ARANHA; LOPES, 2019). The participants are three pairs of learners who interact both in Portuguese and in English. Results showed that more explicit types of reformulations may be face threatening and, in these cases, learners use strategies to save their own faces. On the other hand, more implicit types of reformulations do not seem to be face threatening and can be compared to strategies used to save other people's face.